The effects of sublethal doses of carbaryl on the biology of Dysdercus cingulatus (Fabr.)(Hemiptera; Heteroptera; Pyrrhocoridae - Chung, Gait Fee (1976)
The effects of sublethal doses of carbaryl on the biology of Oysdercus cingulatus (Fabr.) were investigated in the laboratory. The comparative toxicity of carbaryl against various life-stages of Q. cingulatus (Fabr.) as shown by L050 value was found to be first instar < second instar < third instar < fourth instar < adult male < fifth instar < adult female < gravid female, in increasing order.